Severe asthma and quality of life - Hossny, Elham (World Allergy Organ J, 2017)
Severe asthma has a great impact on the quality of life (QOL) of patients and their families. The magnitude of this morbidity is affected by several personal factors including age. Appropriate asthma control and modifications of social roles and activities are expected to improve QOL. Biologics, primarily monoclonal antibodies, have been developed to target specific pathways and molecules important in the pathogenesis of asthma. The use of biologics has shown some promising effects on the QOL of patients with severe recalcitrant asthma. Other potential measures involve targeting risk factors and comorbidities and improving the levels of adherence to therapy. This article briefly reviews the impact of severe asthma on QOL and the potential methods to combat this morbidity including the available therapeutic biologics.